1999
DOI: 10.1037/0022-0663.91.2.216
|View full text |Cite
|
Sign up to set email alerts
|

School bullies, victims, and aggressive victims: Factors relating to group affiliation and victimization in early adolescence.

Abstract: The occurrence of bullying, victimization, and aggressive victimization was documented in a sample of 5th graders. Bullies comprised about 14% of the sample, whereas aggressive victims and victims comprised, respectively, 5% and 18%. Bullying and aggressive victimization was positively related to youngsters' emotionality and activity and negatively related to peer popularity. Although proactive and reactive aggression was related to bullying scores within the group of bullies, only proactive aggression was rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

34
481
5
46

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 563 publications
(566 citation statements)
references
References 39 publications
34
481
5
46
Order By: Relevance
“…There is a diverse body of evidence suggesting that negative social interactions are experienced more intensely when they take place publicly. Studies of bullying, for example, show that bullying has more detrimental effects when the bully acts in front of peers, compared to when the bully and the victim are alone (Pellegrini, Bartini, & Brooks, 1999;Sticca & Perren, 2013). This is also the case when the onlookers do not take part in the bullying (Sticca & Perren, 2013), which indicates that the publicity itself is the exacerbating factor.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…There is a diverse body of evidence suggesting that negative social interactions are experienced more intensely when they take place publicly. Studies of bullying, for example, show that bullying has more detrimental effects when the bully acts in front of peers, compared to when the bully and the victim are alone (Pellegrini, Bartini, & Brooks, 1999;Sticca & Perren, 2013). This is also the case when the onlookers do not take part in the bullying (Sticca & Perren, 2013), which indicates that the publicity itself is the exacerbating factor.…”
mentioning
confidence: 89%
“…To summarize the findings presented above, laughter can also carry negative meaning, and in the case of negative social interactions such as altercations (Mann et al, submitted), bullying (Pellegrini et al, 1999), and exclusion (Klages & Wirth, 2014), the presence of laughing others enhances reported negative experience of the social interaction, as well as the negative response to the interaction. The amplified negative consequences of adverse social interactions accompanied by laughter can result from two different pathways.…”
mentioning
confidence: 99%
“…Because peers have such a critical socialization role during childhood and adolescence (Brown, Eicher, & Petrie, 1986), peer relationships are likely implicated in the consideration of risks and protective processes related to victimization. Researchers have found that poor peer relationships place youth at risk for victimization, while having close friends protects against victimization within the general population (Delfabbro et al, 2006;Forero, McLellan, Rissel, & Bauman, 1999;Nansel et al, 2001;Pellegrini & Bartini, 2000;Pellegrini, Bartini, & Brooks, 1999;Williams & Guerra, 2007).…”
mentioning
confidence: 99%
“…Los investigadores proponen: víctima, matón, reforzador del matón, asistente del matón, defensor de la víctima, outsider o testigo y víctima agresiva, esta última también conocida como víctima provocativa, bully victim o víctima reactiva (Olweus, 1993(Olweus, /2002Orpinas & Horne, 2006;Pellegrini, Bartini & Brooks, 1999;Raine et al, 2006;Salmivalli, Kaukiainen, Voeten & Sinisammal, 2004;Solberg, Olweus & Endresen, 2007). Estas últimas corresponden a víctimas que son rechazadas por su poca adaptación social e incluso hostilidad, motivo por el cual provocan la agresividad de los demás y responden de igual manera, siendo tanto víctimas como victimarios.…”
Section: Definicionesunclassified